Identifying crisphead lettuce genotypes for a wider range of environments - Tobar-Tosse, Dora Enith [UNESP]; dos Santos Candido, Willame [UNESP]; da Silva Santos, Lucas [UNESP]; Castoldi, Renata [UNESP]; Silva, Edgar Henrique Costa [UNESP]; Braz, Leila Trevisan [UNESP] (Corporacion Colombiana de Investigacion Agropecuaria (Corpoica), 2022)
This work aims to select crisphead lettuce (Lactuca sativa L) genotypes superior in production, stability, and adaptability using a mixed model method: restricted maximum likelihood/best linear unbiased prediction. Ten genotypes were grown in different municipalities of the State of São Paulo, Brazil, and seasons of the year, resulting in twelve different environments. The experiment has a randomized complete block design with four repetitions. Genotypes comprise eight breeding lines and two commercial cultivars, Vanda and Vera. The evaluated traits include total production in g/plant, commercial production in g/plant, and numbers of leaves/plant. Analysis of joint deviance indicated that the genotypes responded differently to the environments evaluated. The crisphead lettuce breeding lines that were most productive, stable, and adapted to the twelve lettuce-growing environments, even outperforming the commercial Vanda and Vera cultivars, were lines L8, L2, and L6.
Identificación de genotipos de lechuga crespa cultivados para un amplio rango de ambientes
Keywords: Genotype-environment interaction; genotypic values; Lactuca sativa; REML/BLUP; stability and adaptability